Volcanic Ash Density - Lau, W S; Grainger, R G; Taylor, I (University of Oxford, 2023)
Unsieved ash density measurements from 23 unsieved raw ash samples originating from 15 volcanoes, including mass of sample measured with a digital scale and volume measured with a nitrogen gas pycnometer. Data measured in July-August 2022.